Photodynamic Therapy for Diffuse Choroidal Hemangioma in Sturge-Weber Syndrome - Sílvia Monteiro; Inês Casal; Marinho Santos; Angelina Meireles (Case Reports in Medicine)
Purpose. To report the treatment outcome of photodynamic therapy with verteporfin (PDT) for exudative retinal detachment (RD) associated with diffuse choroidal hemangioma in Sturge-Weber syndrome (SWS). Methods. An interventional case report of a 10-year-old girl with SWS who developed an exudative RD (visual acuity hand motions) that was treated with PDT. She was treated with a first session of multispot PDT. Posteriorly, a choroidotomy for drainage of subretinal fluid was created, combined with an intravitreal injection of gas (SF6) and cryoapplication. Finally, a second session of PDT was applied. Results. Subretinal fluid resolved over a period of one year and visual acuity increased to 20/125. Conclusions. PDT is an effective therapeutic option for exudative RD associated with diffuse choroidal hemangioma.